Hubungan Perilaku Keluarga Dengan Pencegahan Kejadian Demam Berdarah Dengue (DBD) Di Kelurahan Jambangan Kota Surabaya - Andi Jayawardhana; Roby Aji Permana; Yus Kogoya (NERSMID : Jurnal Keperawatan dan Kebidanan, 2019)
Dengue Hemorrhagic Fever (DHF) still occurs in Indonesia. This disease can affect everyone, especially in children. To prevent dengue disease most important is to control the aedes aegypti mosquito as the main vector. Prevention is the program of Eradication Mosquito Nest (PSN) by physical and chemical. Eradication and prevention of disease is needed a good behavior on the community, so that disease prevention efforts can run well. The purpose of this research is to know "Family Behavior Relationship in Prevention with Dengue Hemorrhagic Fever (DBD) in RT 1 RW 2 Jambangan 3A. Kelurahan Jambangan city Surabaya. This research is a qualitative research with "Cross Sectional" design. The sample of this research is 69 people in RT 1 RW 2 urban village of surabaya city with sampling with simple radom sampling technique. Data collection tool used in this research is in the form of questionnaire Family behavior about prevention of DHF and Dengue fever occurrence dengue DBD containing efforts of respondents in prevention of DHF. The analysis tool used chi square test. The results showed that many respondents have the level of family behavior about the disease dbd bad category with the number of 14 residents (20%). Prevention effort as the incidence of DHF disease conducted by many respondents still less that is 23 citizen (33%). Result of hypothesis test of research data aimed sig value. (2 tailed) = 0.000 with p